HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN MOTIVASI KERJA PENDIDIK DI MTs NEGERI 1 KOTA PAYAKUMBUH - Ahmad Arif; Elvi Deswita; Demina Demina (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
This research was motivated because the motivation of educators in MTsN 1 Payakumbuh City is not very good because there are still educators who cannot be disciplined, educators who are often late absent, this is seen from the recap of absences every month. Educators who want to go home fast, educators who are slow to collect devices, educators' motivation to teach is lacking and this relates to the leadership of the principal himself. The limitations of the problems of this research are (a) Leadership of the principal in MTsN 1 Payakumbuh City, (b) Motivation of educators in MTsN 1 Payakumbuh City, (c) The relationship between the leadership of the principal and the motivation of educators in MTsN 1 Payakumbuh City. This research aims to determine whether there is a positive and significant relationship between the principal's leadership and the work motivation of educators in MTsN 1 Payakumbuh City. The hypothesis proposed is that there is a positive and significant relationship between the principal's leadership and the work motivation of educators in MTsN 1 Payakumbuh City. In this study there are two variables, namely the independent variable (principal's leadership) and the dependent variable (educator's work motivation). This research is a field research using a quantitative approach. This research method uses the correlational method. The population in this study was 54 educators and the total sample of 54 educators was taken using the total sampling technique. The research instrument used 2 (two) questionnaires, namely questionnaires about the principal's leadership and educators' work motivation. Data was processed using the Statistical Product and Service Solution (SPSS) program version 20.00, and analyzed using the Karl Pearson Product Moment Correlation Coefficient formula. The results showed that from the results of Pearson Correlation at rxy = 0.627 greater than r table for significant 1% = 0.354 and 5% = 0.273, thus Ha was accepted and H0 was rejected, meaning that there was a positive and significant relationship between the principal's leadership and the motivation of educators in MTsN 1 Payakumbuh City. And from the results of Pearson Correlation on r count = 0.627 can see the level of relationship in the classification of correlation numbers, 0.627 is located between 0.60 to 0.799 with a strong correlation level. Thus, it can be seen that the level of correlation between the principal's leadership and the work motivation of educators in MTsN 1 Payakumbuh City as much as r2 = 36% while 60% is determined by other factors.